Non-nutritive sweeteners and body weight in children with type 1 and type 2 diabetes: a critical narrative review of current evidence, methodological challenges, biological mechanisms, and clinical implications - Sousana K. Papadopoulou; Exakousti-Petroula Angelakou; Theodosios Koimtsidis; Eleni Pavlidou; Dimitrios Tasoulas; Constantinos Giaginis (Frontiers in Nutrition, 2026)
Introduction Body weight management is an important component of pediatric diabetes care, although its clinical relevance differs between type 1 diabetes (T1D) and type 2 diabetes (T2D) because of distinct pathophysiology, insulin physiology, and therapeutic goals. Non-nutritive sweeteners (NNSs) are widely used to replace added sugars, reducing glycaemic load and, in some settings, energy intake. However, their long-term effects on body weight in children with diabetes remain controversial. This narrative review evaluates current evidence on the association between NNS consumption and body weight in children with T1D and T2D, summarizes proposed biological mechanisms, and discusses methodological and clinical implications. Methods A comprehensive narrative literature search identified studies published through April 2026. Randomized controlled trials (RCTs), observational studies, systematic reviews, and meta-analyses evaluating NNS consumption and body weight in pediatric populations were included. Given the limited diabetes-specific evidence, relevant mechanistic findings from adult, animal, and in vitro studies were also considered. Evidence was synthesized according to study design, diabetes type, biological mechanisms, methodological limitations, and clinical relevance. Results RCTs, conducted mainly in general pediatric populations, suggest that replacing sugar-containing foods and beverages with NNS-containing alternatives may modestly reduce short-term energy intake and attenuate weight gain, whereas long-term effects remain inconsistent. Observational studies frequently report positive associations between NNS consumption and higher BMI or adiposity, although these findings are likely explained by reverse causality, residual confounding, exposure misclassification, and methodological differences. Evidence in children with diabetes is scarce, heterogeneous, and rarely distinguishes between T1D and T2D. Proposed mechanisms include alterations in appetite regulation, reward processing, energy compensation, gut microbiota, and incretin and insulin responses, but human evidence remains inconsistent and does not demonstrate clinically meaningful long-term effects on body weight. Conclusion Current evidence does not support a consistent or clinically meaningful long-term effect of NNS consumption on body weight in children with T1D or T2D. Although NNSs may reduce sugar intake and improve short-term glycaemic management, they should be viewed as adjunctive dietary tools rather than primary weight-management interventions. Future well-powered, long-term studies should evaluate individual sweeteners separately and distinguish between diabetes types to inform diabetes-specific dietary recommendations.